Pengaruh kualitas produk dan citra merek terhadap kepuasan pelanggan melalui keputusan pembelian sebagai intervening - Salman Paludi; Siti Nurchorimah (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2021)
The purpose of this research is to analyze the influence of product quality and brand image on customer satisfaction through purchasing decisions as intervening variable. The population in this study was STIE Pariwisata Internasional (STEIN) students who used Logitech products more than twice. The number of samples taken was as many as 180 respondents with purposive sampling technique.Data analyze by descriptive and quantitative. The quantitative analysis using Structural Equation Modeling (SEM). The result of this study indicate that product quality has an effect on purchase decision, brand image has an effect on purchase decision, product quality has an effect on customer satisfaction, brand image has an effect on customer satisfaction, purchase decision has an effect on customer satisfaction. Additionally, there is does not have a significant indirect effect between product quality on customer satisfaction through purchase decisions, there is an indirect effect between brand image on customer satisfaction through purchase decisions. Keywords: Product quality; brand image; purchase decision customer satisfaction. TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//